Validitas modul fisika bemuatan literasi saintifik pada materi besaran dan pengukuran serta vektor - dwi putri ramadhani; renol afrizon; hidayati hidayati (PILLAR OF PHYSICS EDUCATION, 2019)
In 21st century education requires the produced of quality human resources. The emphasized skills are students have the ability to think critically and solve problems, communicate and cooperate, create and renew, and literacy skills. The government's efforts in answering the demands of 21st century education are by implementing the 2017 revised 2017 curriculum. The reality in school showed that physics learning has not been implemented well, one of student’s literacy is still low. One solution to develop physics teaching materials with scientific literacy. The purpose of this study was to determine the validity of physics teaching materials with scientific literacy.Type of research was Research and Development (R & D). The object of this research was physics teaching material that contains scientific literacy in matter of scale, measurement and vectors. Sources of data from this study were obtained from the results of validation of teaching materials. The validation results were obtained from three  physics lecturers. The data collection instrument used was a validity test sheet to determine product validity. Data analysis technique used was descriptive statistical analysis of the results of product validation. Based on the analysis of the data from the research,it can be concluded physics teaching materials with scientific literacy on the material quantities and measurement, vector have validity with category very high with an average validation value of 88.73.